Computer Network Training "Building Creativity through Wifi Corner Networks in the Digital Era" - Ahlis Noor Kholili (Jurnal Pengabdian kepada Masyarakat (DIASYA), 2025)
The development of digital technology affects various aspects of life, including education. The need for adequate internet access is a challenge in itself, especially in schools that have limited network infrastructure. NU Al Hidayah Vocational School faces the problem of minimal understanding of students regarding computer network technology, which has an impact on limited use of the internet in learning activities. To overcome this problem, community service was carried out in the form of computer network training with the theme "Building Creativity through Wifi Corner Networks in the Digital Era". This training aims to provide basic understanding and practical skills to participants in building and managing a Wifi Corner network as an innovative digital solution. This activity is carried out through several stages, starting from identifying needs, providing materials, direct practice, to evaluation and mentoring. The results of the training showed an increase in participants' understanding and ability to manage computer networks independently. Apart from that, the Wifi Corner network built during the training was successfully implemented and used to support learning. In conclusion, this training had a positive impact on increasing the digital literacy of students, as well as creating a technology-based learning ecosystem at SMK NU Al Hidayah. This training can be a relevant model of community service to improve information technology skills in the educational environment